PENGARUH BRAND IMAGE, KUALITAS PRODUK, DAN HARGA TERHADAP KEPUASAN KONSUMEN - Fadali Rahman; Bunga Mawar Mira; Rysca Alvia; Adinda Nabilla Abdilla Putri; Lutfiadi; Ria Rachmawati (Jurnal Riset Multidisiplin Edukasi, 2025)
This study aims to analyze the impact of Brand Image, product quality, and price on customer satisfaction. These three factors are considered crucial in shaping consumer perception and influencing their purchasing decisions. The findings show that a strong Brand Image can enhance the positive perception of product quality, while competitive pricing plays an important role in creating the value desired by consumers. The interaction between these three factors significantly contributes to customer satisfaction, which in turn can increase loyalty and product recommendations. These findings provide practical insights for companies in formulating effective marketing and branding strategies to improve customer satisfaction.